Forecasting electricity consumption in Pakistan: the way forward. (March 2016) - Hussain, Anwar; Rahman, Muhammad; Memon, Junaid Alam
Abstract: Growing shortfall of electricity in Pakistan affects almost all sectors of its economy. For proper policy formulation, it is imperative to have reliable forecasts of electricity consumption. This paper applies Holt-Winter and Autoregressive Integrated Moving Average (ARIMA) models on time series secondary data from 1980 to 2011 to forecast total and component wise electricity consumption in Pakistan. Results reveal that Holt-Winter is the appropriate model for forecasting electricity consumption in Pakistan. It also suggests that electricity consumption would continue to increase throughout the projected period and widen the consumption-production gap in case of failure to respond the issue appropriately. It further reveals that demand would be highest in the household sector as compared to all other sectors and the increase in the energy generation would be less than the increase in total electricity consumption throughout the projected period. The study discuss various options to reduce the demand-supply gap and provide reliable electricity to different sectors of the economy. Highlights: We forecast total and component wise electricity consumption for Pakistan. Electricity shortfall in Pakistan will increase in future if same situation exists. Various options exist to cope with the electricity crisis in the country. Holt-winter model gives best forecasts for electricity consumption in the country.